1920
DOI: 10.1002/cber.19200530917
|View full text |Cite
|
Sign up to set email alerts
|

Das Schmelzen der Sulfide von Zink, Cadmium und Quecksilber

Abstract: Bleiwasserstoff wichfg, weil hier schon vom dritten Glied, dem G e r m a n i u m w a s s e r s t o f f , nicht einmal die Formel als experimentell gut gesichert gelten kann I). Beim Blei-, Wismut-und Polonium-wasserstolF werden auBerdem ihre Beziehungen zur Emanation von besooderem Interesse sein , da bekanntlich die Halogengruppe i n der finften Periode keinen Vertreter mehr hat und alle zwisehen Hydriden und Edelgaeen gefundenen GesetzmiiBigkeiten bisher nur in vier Perioden gepruft werden konnten. Einige Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1922
1922
1970
1970

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Bridgman growth under high inert gas pressure.--Tiede and Schleede (8) found that ZnS and CdS could be melted by retarding the decomposition with high nitrogen pressure. We found this method to work only for II-u compounds, where cation and anion are similar in volatility.…”
Section: Resistance Heater Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bridgman growth under high inert gas pressure.--Tiede and Schleede (8) found that ZnS and CdS could be melted by retarding the decomposition with high nitrogen pressure. We found this method to work only for II-u compounds, where cation and anion are similar in volatility.…”
Section: Resistance Heater Methodsmentioning
confidence: 99%
“…Moreover, one observes the same emission if one reduces the radical cation of rubrene in a homogeneous reaction using some suitable reductant (5). Several studies have shown that this kind of chemiluminescent electrontransfer reaction is common among aromatic hydrocarbons and their derivatives and also among sev~eral heterocycles (2,(6)(7)(8). Since the reactants are most easily generated and studied electrochemically, this phenomenon has become known as "electrogenerated chemiluminescence" (ECL).…”
Section: Magnetic Field Effects On Some Fluid-solution Processes Invo...mentioning
confidence: 99%
“…Electroluminescence (1,2) shows a characteristic slow decrease in light emission, in common with all other practical light sources, over long periods of operation of the lamp. Improvements in the maintenance of electroluminescence have kept pace with increases in brightness and efficiency and have required knowledge of the dependence of electroluminescence maintenance on phosphor properties, conditions of operation, and lamp construction.…”
Section: Electroluminescence Maintenancementioning
confidence: 99%
“…Tiede and Schleede (2) observed that the fluxing agent promotes crystal growth at low temperatures by lowering the melting point of the base material. The average particle size of the zinc sulfide crystallites increases during this treatment, and the final particle size depends on the processing conditions 1 Present address: Republic Aviation Corp., Farmingdale, N. Y. and the additives.…”
mentioning
confidence: 99%
See 1 more Smart Citation